Performance and Factors Inhibiting Research and Scientific Publication of Universitas Terbuka Indonesia Lecturers - Tri Yulianto; Vishnu Juwono (Publik : (Jurnal Ilmu Administrasi), 2021)
Efforts to improve the performance of research and scientific publications in Indonesian universities are still a challenge. Various problems often become an inhibiting factor for lecturers' research performance. This study analyzes how the performance and factors were inhibiting the performance of research and scientific publications at the Universitas Terbuka, which is the only Open and Distance Learning Higher Education institution (PTTJJ) in Indonesia. The research method used is qualitative descriptive. The results showed that although the number of research and journal publications increased during 2017-2019, the performance of research and scientific publications of Universitas Terbuka lecturers has not been optimal. Of the five factors are considered as obstacles, three of which are factors that are generally also found in other universities, namely the lack of competence and motivation of lecturers in researching, lack of research/laboratory support facilities, and the research culture among lecturers has not yet developed well. Meanwhile, two other factors were different findings, namely the issue of lecturer recruitment and development policies in the early days of the establishment of the Universitas Terbuka, which was not in line with the needs of the study program, and the problem of characteristics and workload of PTTJJ lecturers which are different from conventional university lecturers. Universitas Terbuka lecturers are not only obliged to carry out the tri dharma functions of higher education but they are also burdened with tasks related to the management of PTTJJ or quite a lot of academic administrative work.